STUDYING OF THE COMPONENT OF NUTRIENTS AND HEAVY ELEMENTS IN DUCKWEED AND ITS PRODUCTIVITY WITHIN REGIONS AND SEASONS UNDER NATURAL CONDITIONS IN BAGHDAD CITY - Hasham Abd Al-Rasiak (Mesopotamia Journal of Agriculture)
The studying in some local aquatic plants was known as the duckweed Lemna sp. in natural conditions during four seasons in various regions of Baghdad, the components of nutrients in the duckweed plant were varied with regions and these were a significant variations of protein ratios 13.30-55.00%, ash 18.25-24.96%, carbohydrates 16.35-50.37%, fat 0.05-2.60% Fiber 3.53-9.23% abd moisture 5.55-7.60%, the concentration of heavy elements significant variations at the plant where zinc concentration was between 36.21-83.01 mg/kg, iron between 2979.24-969.18 mg/kg, lead between 0.79-104.06 mg/kg and copper between 1.69-12.39 mg/kg, the productivity of duckweed was moral variations within regions and seasons, spring marked the highest productivity was the Zaafaraniya and was at least for the winter in Dowra. We Concludes from the studying of plant duckweed water; it could be obtained throughout the year depending on the suitable climatic conditions in our country is Iraq, as well as a source of high-value food feeder.